(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Blunt laryngotracheal injuries are rare. The signs and symptoms of blunt laryngotracheal trauma are not always specific to the extent or type of injury. A high index of suspicion should exist in any injury that may be associated with airway trauma. We report a 30-years man who had progressive shortness of breath following blunt neck injury. He had massive emphysema whereby an emergency tracheostomy with multiple fasciotomy was performed. During emergency tracheostomy, it was noted that he had anterior cricotracheal separation which was communicated posteriorly by mucosa and trachealis muscle. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 114-118